PEDAGOGICAL ASPECT OF CLASSROOM LANGUAGE USED BY THE TEACHER OF INTELLECTUALLY DISABLED STUDENTS IN TEACHING ENGLISH (RETAIN, 2017)
PEDAGOGICAL ASPECT OF CLASSROOM LANGUAGE USED BY THE TEACHER OF INTELLECTUALLY DISABLED STUDENTS IN TEACHING ENGLISH Nur Setyo Wulandari English Education, Language and Art Faculty, Surabaya State University sagayuki3@gmail.com Nur Chakim, S.Pd., M.Pd. English Education Department, Language and Art Faculty, Surabaya State University hakimnur_24@yahoo.com Abstrak Bahasa kelas adalah bahasa yang digunakan oleh guru yang mengajar Bahasa Inggris sebagai bahasa asing baik menggunakan bahasa ibu atau Bahasa Inggris itu sendiri. Penggunaan bahasa kelas tidak hanya digunakan untuk mengajar siswa normal pada umumnya namun juga digunakan untuk mengajar siswa berkebutuhan khusus. Penelitian ini bertujuan untuk menyelidiki penggunaan aspek pedagogi dari bahasa kelas oleh guru yang mengajar siswa tuna grahita Bahasa Inggris mengingat siswa tersebut memerlukan perlakuan yang berbeda sesuai dengan tingkat kesulitan yang berbeda dari siswa normal. Penelitian ini juga bertujuan untuk menginfestigasi respon siswa tuna grahita terhadap aspek pedagogi yang digunakan oleh guru dalam aktifitas di dalam kelas. Penelitian ini menggunakan deskriptif kualitatif sebagai rancangan penelitian. Subjek penelitian adalah guru yang mengajar siswa tuna grahita dan siswa tuna grahita yang berada dalam satu kelas dengan siswa berkebutuhan khusus lainnya. Guru dan siswa diobservasi dan direkam selama proses belajar-mengajar di dalam kelas untuk pengumpulan data. Terdapat dua hasil mendasar dalam penelitian ini. Pertama, aspek pedagogi pada bahasa kelas seperti mode operatif, mode interaktif, dan mode informatif digunakan oleh guru dalam berbagai kegiatan. Mode operatif sering digunakan oleh guru ketika meminta siswa untuk menulis, membaca, maju ke depan, dan mengerjakan latihan. Mode ini juga digunakan oleh guru untuk membantu siswa ketika mengalami kesulitan dalam membaca dan menulis, digunakan untuk mengingatkan siswa untuk mengerjakan latihannya sendiri, dan mengulas materi. Mode interaktif digunakan guru dalam menanyai siswa perrihal hari dan tanggal, tujuan pembelajaran, kosa kata, memeriksa ingatan siswa, dan mengulas materi. selanjutnya, mode informatif digunakan oleh guru untuk memberitahu siswa mengenai tujuan pembelajaran, memperkenalkan kosa kata baru, dan membantu siswa dalam membenarkan kesalahannya. Data yang diperoleh dari catatan lapangan menunjukkan bahwa guru lebih sering mengulang ungkapan-ungkapan dari mode tersebut. Kedua, siswa memberikan respon negatif dan respon positif terhadap aspek pedagogi yang digunakan oleh guru. Kata Kunci : tuna grahita, bahasa kelas, aspek pedagogi Abstract Classroom language is language expressions which are used by the foreign language teacher in EFL teaching process both L1 and L2. The use of classroom language in teaching English is not only used for normal students but also used for disability students. This research is aimed to examine the use of pedagogical aspect of classroom language by the teacher of intellectual disabled students in teaching English since they need different treatment in which they have different difficulties from normal students. This research is also attempting to investigate the intellectual disabled students’ responses toward the teacher’s pedagogical expressions in the classroom activities. The base of this study is using descriptive qualitative as research design. A teacher of intellectually disabled students was selected as a subject of this study. Further, three intellectually disabled students who are in the same class with other disabilities students were also selected as the subjects of this study. The teacher and the students were observed and recorded during teaching-learning process to gain the data. There were two result of this study. First, the pedagogical aspect of classroom language such as operative mode, interactive mode, and informative mode used by the teacher in many cases. The expressions of operative mode were used by the teacher mostly to give direction for the students such as writing, reading, coming forward, and doing the exercise. The expressions also used by the teacher to help the students who have difficulties in reading and writing, warn the students, and review the materials. Further, the expressions of interactive mode was used by the teacher to ask something such as asking date and day, asking learning objective, asking the vocabularies, checking the students memory, and reviewing the materials. Additionally, the expression of informative mode was used by the teacher to tell the learning objectives, introduce the new vocabularies, and correct the students’ mistake. The data from the field note showed that the teacher mostly repeated the expressions of those modes. Second, the students gave negative and positive responses toward teacher’pedagogical aspect. Keyword: intellectually disabled students, classroom language, pedagogical aspect